Pelatihan Reference Managemenet Software (RMS) Zotero dalam pengelolaan Sumber Rujukan Penelitian - Muhammad Asy’ari; Hunaepi Hunaepi; Baiq Mirawati; Armansyah Armansyah; Helmi Rahmawati (Sasambo: Jurnal Abdimas (Journal of Community Service), 2022)
Kurangnya pemahaman dan keterampilan mahasiswa dalam menggunakan Reference Managemenet Software (RMS) Zotero menjadi kendala dalam menyusun sumber pustaka yang sistematis dan presisi. Pengabdian Kemitraan Masyrakat ini bertujuan untuk meningkatkan pemahaman dna keterampilan mahasiswa pendidikan biologi menggunakan Reference Managemenet Software (RMS) Zotero dalam pengelolaan sumber rujukan. Mitra dalam kegiatan ini adalah mahasiswa semester enam program studi pendidikan biologi Universtas Pendidikan Mandalika, jumlah mitra yang terlibat 6 orang mahasiswa. Metode pelaksanaan adalah knowledge transfer dan Model Community development  dengan tahapan kegiatan; 1) plan, 2) implementation, dan 3) evaluation. Setelah kegitan dilaksanakan terdapat peningkatan pemahaman dan keterampilan mitra dalam memanfaatkan  Reference Managemenet Software (RMS) Zotero dalam pengelolaan sumber rujukan. Keterampilan menggunakan RMS Zotero penting untuk dimiliki oleh mahasiswa yang sedang menempuh matakuliah tugas akhir, sehingga materi tetang RMS Zotero ini perlu menjadi salah satu  pokok bahasan dalam mata kuliah teknik penulisan artikel ilmiah. Zotero Reference Management Software (RMS) training in managing Research Reference Sources for Biology Education Students The lack of students' understanding and skills in using Zotero's Reference Management Software (RMS) becomes an obstacle to compiling systematic and precise library sources. This Community Partnership Service aims to improve the understanding and skills of biology education students using Zotero's Reference Management Software (RMS) in managing referral sources. Partners in this activity are sixth-semester students of the Biology education study program at the Mandalika Education University, the number of partners involved is 6 students. The implementation method is a knowledge transfer and Community development model with activity stages; 1) plan, 2) implementation, and 3) evaluation. After the activity was carried out there was an increase in partners' understanding and skills in utilizing Zotero's Reference Management Software (RMS) in managing referral sources. The skill of using RMS Zotero is important for students who are taking final project courses, so this material about RMS Zotero needs to be one of the topics in the technical article writing engineering course.